De la lex scantinia aux récents amendements du Code criminel: homosexualité et droit dans une perspective historique - Demers, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
This paper deals with the legal approach to homosexuality throughout history, focussing on Roman law, French law up to the Revolution, English law till the mid-60's and finally, Canadian law from the French period up to the amendments to the Criminal Code in 1969. What lessons can be drawn from this analysis? A first conclusion is the increasing intolerance towards homosexuals as evidenced by laws that become more and more preoccupied with private morality and control of individual behaviour. Here, we notice the inverse trend in the Roman law tradition and the common law one, where cultural and religious differences explain much of this curious evolution. A second conclusion is the link established between deviant behaviour and all forms of « deviance » from official policies-thus, accusations of homosexuality are to be found in troubled periods of religious (heresies) and political turmoil. Finally, one notes that although the Medieval period is often considered as being particularly cruel in its treatment of homosexuals, this view would need important qualifications in light of the 20th century treatment of such persons, witness of course, the Nazi extermination.